Yak- the “almighty livestock” of the rugged Himalayan Mountains - Loat, Shubham; Pukhrambam, Martina; Mepfhuo, Khriengunuo; Medhi, Dinamani; Paul, Vijay; Hussain, Mokhtar; Jatana, Mansukh Singh; Bhatt, Ninad; Sarkar, Mihir (Journal of Livestock Biodiversity, 2025)
The yak is a remarkable animal because of its distinct physical and structural characteristics that allow it to adapt to the rugged mountains with unfavourable climate. Yaks are regarded as the “almighty livestock” by the herding communities since they are deeply ingrained in the customs, socio-economic processes, and culture. Yaks are well adapted to the harsh climate and hypoxia occurring under high altitude grazing conditions of the Himalayan Mountains. However, it is unclear to which degree different types of hybrids of yaks and cattle, common in the Himalayas, tolerate these conditions and how they perform and behave under these circumstances. Therefore, in this review we are going to discuss some of the mechanisms for their adaptation in the harsh climatic conditions.